New Insights into Probabilistic Thinking: A Study of Cognitive Styles and Probability Problem-Solving among Masculine Male Students - Supratman; Enda budi rahaju; I Ketut Budayasa (International Journal of Ethno-Sciences and Education Research, 2026)
This study investigated a new insight into the probabilistic thinking of male mathematics education students with Field-Independent cognitive style. One student with masculine male and a Field-Independent cognitive style (MLI) based on the GEFT test and a gender questionnaire, while also considering mathematical ability assessed through UTBK SBMPTN questions. From 20 students with medium-level mathematical ability, MLI was chosen to participate in a probability problem-solving test conducted at the Faculty of Teacher Training and Education, Universitas Sembilanbelas November Kolaka. This research employed a descriptive qualitative method with a case study design. The results indicate that MLI's probabilistic thinking is highly proficient. Based on Polya’s four problem-solving stages, MLI effectively identified given information, recorded data accurately, and answered in a structured manner, although he did not explicitly write the combination formula or binomial distribution. In the "looking back" stage, while MLI did not rewrite the final answer, interviews confirmed that he had rechecked his work, verifying each step to obtain the correct probability value